(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Speech problems in children are one of the most widely studied topics in science. Performing speech exercises from a child’s early age can prevent him or her from developing speech-related defects in the future. In this article, the author describes in detail the work on speech defects in children, the use of innovative technologies in their treatment